Pentingnya Pendidikan Karakter Pada Anak Sekolah Dasar Di Zaman Serba Digital - Rubiani, Rubiani (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Character education is an attempt to apply religious values, morals, ethics to students through science, assisted by parents, teachers, and the community which is very important in the formation and development of students' character. Every child has good potential from birth,but this potential must be honed and socialized properly so that the character of each child is formed and developed to its full potential. In this digital era, children easily use digital media. The digital age which not only has positive impacts, but also negative impacts becomes its own task for educators, parents and adult communities in guiding and monitoring what children do with these digital media, so that children are able to utilize their digital media as much as possible and get the benefits that they can both for himself and his life.